Pengaruh Metode Estafet Jawaban terhadap Peningkatan Hasil Belajar Berdasarkan Analisis N-Gain pada Siswa Kelas X di SMAN 1 Menganti - Nanang Abdillah; Nur Lailiyah; Intan Laily Agustin; Naila Ahsana Nadia; Nisful Laila El Rahma Ramadhani; Muhimmatul Adillah Noor; Kharisma Dewi Masyithoh; Muhammad faid nailul murod (HORIZON: Indonesian Journal of Multidisciplinary, 2026)
This study aims to examine the effect of the relay answer method on improving the learning outcomes of Grade X students at SMAN 1 Menganti. The background of this research is based on the importance of implementing learning methods that actively engage students in the learning process, not only focusing on one-way knowledge transfer but also encouraging interaction, collaboration, and individual responsibility within group learning activities. This study employed a quantitative approach using a quasi-experimental design. The results of the study indicate that there is a difference in learning improvement between the class that applied the relay answer method and the class that used conventional learning methods. Data analysis shows that the relay answer method has a significant effect on improving students’ learning outcomes. In addition, classroom observations reveal that this method enhances student learning activities, creates a more interactive learning environment, and encourages active participation in group work. Based on these findings, it can be concluded that the relay answer method is effective in improving the learning outcomes of Grade X students at SMAN 1 Menganti. Therefore, this method can be considered as an alternative learning strategy to enhance both the learning process and students’ academic achievement